N2O emissions from a cultivated Mollisol: optimal time of day for sampling and the role of soil temperature - Cosentino, Vanina Rosa Noemi (2012)
The correct use of closed field chambers to determine N2O emissions requires defining the time of day that best represents the daily mean N2O flux. A short-term field experiment was carried out on a Mollisol soil, on which annual crops were grown under no-till management in the Pampa Ondulada of Argentina. The N2O emission rates were measured every 3 h for three consecutive days. Fluxes ranged from 62.58 to 145.99 μg N-N2O m-2 h-1 (average of five field chambers) and were negatively related (R2 = 0.34, p < 0.01) to topsoil temperature (14 - 20 oC). N2O emission rates measured between 9:00 and 12:00 am presented a high relationship to daily mean N2O flux (R2 = 0.87, p < 0.01), showing that, in the study region, sampling in the mornings is preferable for GHG.